Analysis Of The Financial Performance Of The Company Cooperative PT. Bangun Rasaguna Lestari - Laowo, Forfalenti; Fatihah, Dian Candra (Transforma Jurnal Manajemen, 2025)
Cooperatives play an important role in supporting the welfare of their members, especially among lower to middle-income communities. This study aims to analyze the financial performance of the Savings and Loan Cooperative (KSP) PT. Bangun Rasaguna Lestari from 2021 to 2024 by using liquidity, solvency, and profitability ratios. The research method used is qualitative descriptive with an analysis of the cooperative's financial statements based on the cooperative health assessment standards from the Ministry of Cooperatives and SMEs results show that the cooperative has very healthy liquidity and solvency, with a current ratio above 457.25% and a debt to asset ratio below 20%. However, the cooperative's profitability performance remains less than optimal, with an average return on equity of around 9.3%, below the expected standard. This condition indicates that the cooperative is able to meet its short-term obligations and maintain financial stability, but still needs to improve operational efficiency and capital utilization to generate higher profits for sustainable business growth and member welfare.